ประสิทธิภาพการจัดการน้ำด้วยวิธีแบบเปียกสลับแห้งต่อการเจริญเติบโต และผลผลิตข้าว EFFICIENCY OF WATER MANAGEMENT BY ALTERNATIVE WETTING AND DRYING ON RICE GROWTH AND PRODUCTION - บำรุงบุตร, จิตติวรรณ; หาญพัฒนากิจ, พงษ์เทพ; ชิดไธสง, อำนาจ; แสงงาม, สุขุมาภรณ์; วานิชชัง, ศุภิกา (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Alternative wetting and drying (AWD) is an irrigation technique in which water is used to achieve intermittent flooded and non-flooded soil conditions for stimulating rice growth and production. The objective of the current study was to evaluate the potential of water use efficiency on aboveground and belowground growth of rice (Oryza sativa L. cv. RD41) under two AWD conditions. T3, water was allowed to decrease to fifteen centimeters below the soil surface and then water was added to ten centimeters above soil surface and T2, the water level was fifteen centimeters below the surface and then water was added to five centimeters above the surface of the soil. These were compared to the control where water was maintained at ten centimeters throughout the cultivation period (T1). The experiments were conducted at Prachin Buri Rice Research Center, Prachin Buri province during dry season (DS) and wet season (WS). The results showed that the amount of total water use was significantly reduced by 52% in T2 and 32% in T3 compared to the T1. The plant growth and biomass of T1 and T2 were significant different with T3 (p-value<0.05). However, root growth in WS between both AWD treatments and T1 were also significantly different (p-value<0.05). The accumulated root growth for the wet season of T1, T2 and T3 were 8,847, 11,217 and 11,896 km/ha, respectively. The results indicated that both AWD only stimulated belowground growth as root growth and expansion, while root death was similar in all treatments. In addition, the aboveground growth of plant height was correlated with root growth in soil by rapid growth until the tillering stage.